Virtual patient design: exploring what works and why. A grounded theory study. Issue 6 (12th May 2013) - Bateman, James; Allen, Maggie; Samani, Dipti; Kidd, Jane; Davies, David
<x xml:space="preserve">Abstract</x> Objectives Virtual patients (VPs) are online representations of clinical cases used in medical education. Widely adopted, they are well placed to teach clinical reasoning skills. International technology standards mean VPs can be created, shared and repurposed between institutions. A systematic review has highlighted the lack of evidence to support which of the numerous VP designs may be effective, and why. We set out to research the influence of VP design on medical undergraduates. Methods This is a grounded theory study into the influence of VP design on undergraduate medical students. Following a review of the literature and publicly available VP cases, we identified important design properties. We integrated them into two substantial VPs produced for this research. Using purposeful iterative sampling, 46 medical undergraduates were recruited to participate in six focus groups. Participants completed both VPs, an evaluation and a 1‐hour focus group discussion. These were digitally recorded, transcribed and analysed using grounded theory, supported by computer‐assisted analysis. Following open, axial and selective coding, we produced a theoretical model describing how students learn from VPs. Results We identified a central core phenomenon designated 'learning from the VP'. This had four categories: VP Construction; External Preconditions; Student–VP Interaction, and Consequences. From these, we constructed a three‐layer model describing the interactions of students with VPs. The inner layer consists of the student's cognitive and behavioural preconditions prior to sitting a case. The middle layer considers the VP as an 'encoded object', an e‐learning artefact and as a 'constructed activity', with associated pedagogic and organisational elements. The outer layer describes cognitive and behavioural change. Conclusions This is the first grounded theory study to explore VP design. This original research has produced a model which enhances understanding of how and why the delivery and design of VPs influence learning. The model may be of practical use to authors, institutions and researchers.